Pendidikan Multikultural : Membangun Kesatuan dalam Keanekaragaman - Zamzami, Abid Khaidar; Qotrunnadya, Fella Sufah; Muhtar, Aprilia Kartika; Pratama, Ilham Alif; Abdul Khobir (Cendekia Madani Nusantara, 2025)
Indonesia as a nation state that has various differences emphasizes that its citizens must be able to live in situations of these differences. Thus Multiculturalism in Indonesia is something that cannot be avoided. However, in reality, it cannot be denied that the face of Indonesian multiculturalism has so far not been very good and anytime conflicts will arise. The method used in this research is literature which is done by collecting secondary and relevant theoretical data that supports the writing plan. The end of this study is that multicultural education provides an understanding that differences are a divine will that we must be grateful for and how we are able to live in differences with a spirit of tolerance between differences. The success of multicultural education is marked by the community having the knowledge, skills and attitudes that are embodied in a life that is tolerant and not hostile to each other which leads to conflict in differences in terms of ethnicity, religion, culture and so on. Keywords: Education, Multicultural, Unity, Diversity